Filozoficzno-historyczne zaplecze etyki biznesu - Więckowski, Paweł (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2018)
The text describes different philosophical concepts and historically important cultural phenomena that should be considered while rethinking ethical side of business. Broad range of both philosophical (such as the search for the foundations of morality, social contract) and social subjects (such as history of centralized state, individualism) is presented to help the reflections. The background for analysis is the history of culture, especially of primary collective society; contrasted with it is individualism of classical Athens with corresponding reaction of philosophers; development of state and Christianity in Roman Empire; organismic medieval state; Renaissance, reformation and the birth of capitalism; the Enlightenment breakthrough and English capitalism; liberalism and Darwinism of the 19th century; the catastrophe of European culture and success of America of the 20th century.